2010
DOI: 10.1007/s00414-010-0520-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of the nine X-STR loci typing system and genetic analysis in three nationality populations from China

Abstract: This study is to develop a new multiplex polymerase chain reaction (PCR) system that simultaneously amplifies the nine X-chromosome short tandem repeats loci in the same PCR reaction, and to explore their polymorphism and mutation rate among three nationality populations from China. These loci included DXS6854, DXS9902, DXS6809, GATA172D05, HPRTB, DXS7423, DXS6807, DXS8378, and DXS8377. The samples of 890 (484 males and 406 females) unrelated individuals from Guangdong Han population, Xinjiang Uigur, and Inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
4
19
2
Order By: Relevance
“…The one-sided mutation rate  was set equal to 0.001 for all markers, which represents an average of recent estimates for X-STRs [20,21], and which also agrees well with the findings of the present study (see Supplementary Table 1). In fact, we observed 8 mutations in 10,290 informative meioses, which corresponds to a two-sided  of 7.810 -4 (Table 3).…”
Section: Likelihood Maximizationsupporting
confidence: 86%
“…The one-sided mutation rate  was set equal to 0.001 for all markers, which represents an average of recent estimates for X-STRs [20,21], and which also agrees well with the findings of the present study (see Supplementary Table 1). In fact, we observed 8 mutations in 10,290 informative meioses, which corresponds to a two-sided  of 7.810 -4 (Table 3).…”
Section: Likelihood Maximizationsupporting
confidence: 86%
“…Allele 48 was the third frequent in this study with the allele frequency of 0.1450, as shown in Table 2 and Figure 2. This result is similar to the analysis of DXS8377 in populations of Chinese, Japanese and Inner-Mongolia Mongol (China), in which allele 48 was also the third frequent (Table 3) [5,16,17]. Allele 50 was the fourth frequent in this study with the allele frequency of 0.1200, as shown in Table 2 and Figure 2.…”
Section: Populationssupporting
confidence: 89%
“…Previous studies also found allele 51 to be subordinate, including the genetic analysis in populations of Han Chinese, Galicians (Spain) and Slovakians, as shown in Table 3 [7,17,20]. Allele 48 was the third frequent in this study with the allele frequency of 0.1450, as shown in Table 2 and Figure 2.…”
Section: Populationssupporting
confidence: 74%
See 2 more Smart Citations